2023
DOI: 10.3389/fchem.2023.1138057
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, biological and in silico assessment of date (P. dactylifera L.) fruits grown in Ha’il region

Abstract: Background: Dates palm (Phoenix dactylifera L.) fruits are among the most widely used fruits in the Middle East and African nations. Numerous researchers confirmed the presence of phytochemicals in P. dactylifera L. fruit and its by-products with broad-ranging biological activities.Objectives: In the present work, phytochemical and biological assessments of two different cultivars of date fruit (ShishiM1 and MajdoolM2 grown in the Ha’il region of Saudi Arabia) have been carried out.Methods: Date fruits were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…For visualisation and plotting the graphs, Visual molecular dynamics (VMD) and Grace software was employed. Various parameters i. e. RMSF, RMSD, Rg, SASA and hydrogen bond formation were determined through MD simulation to determine the stability of the protein‐ligand complex [47–53] …”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…For visualisation and plotting the graphs, Visual molecular dynamics (VMD) and Grace software was employed. Various parameters i. e. RMSF, RMSD, Rg, SASA and hydrogen bond formation were determined through MD simulation to determine the stability of the protein‐ligand complex [47–53] …”
Section: Materials and Methodologymentioning
confidence: 99%
“…Various parameters i. e. RMSF, RMSD, Rg, SASA and hydrogen bond formation were determined through MD simulation to determine the stability of the protein-ligand complex. [47][48][49][50][51][52][53] Binding Free Energy Calculation…”
Section: Molecular Dynamics (Md) Simulationsmentioning
confidence: 99%
“…The seeds, fruits and pollen extracts demonstrated activity against pancreatic, colorectal, hepatic and lung cancer cell lines. [58,59] Saudi Khalas date fruit ethyl acetate extract exhibited tumor microenvironment modulating effect against pancreatic cancer by the reduction of pancreatic stellate cells' activity, the reversal of their fibrotic phenotype and counteracting TNF-α signaling pathway. [60] The aqueous methanol extract of Ajwa date fruits at Tamr stage prevented in vitro the proliferation of colon cancer cells (Caco-2) as well as improved colon health by increasing the beneficial bifidobacterial and bacteroides growth in healthy volunteers' gut.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…These phytochemical compounds underscore the antioxidant, anti-diabetic, anti-obesity [ 129 ], hepatoprotective [ 130 ] and neuroprotective actions [ 131 ] and anti-lipidemic properties of date fruits, contributing to their overall health benefits in human consumption [ 103 , 120 , 121 , 124 , 132 , 133 ]. The study carried out by Alsukaibi et al, [ 134 ] indicated the presence of various components in date fruits, responsible for cytotoxicity against cancer cells. Dominant phenolic compounds, such as q-coumaric, ferulic, and vanillic acids, were identified.…”
Section: Nutritional and Functional Properties Of Datesmentioning
confidence: 99%
“…Significantly, these extracts displayed extensive antimicrobial activity against various pathogens [ 103 , 120 , 123 ]. Alsukaibi et al, [ 134 ] found that date kernel (seed) is a natural source of polyphenols that have potential antibacterial activity.…”
Section: Nutritional and Functional Properties Of Datesmentioning
confidence: 99%